2014
DOI: 10.1002/hyp.10206
|View full text |Cite
|
Sign up to set email alerts
|

Changing hydrologic connectivity due to permafrost thaw in the lower Liard River valley, NWT, Canada

Abstract: Flows from river basins in northwestern Canada have been rising in the last two decades as a result of climate warming. In the wetland‐dominated basins that characterise the southern margin of permafrost, permafrost thaw and disappearance, and resulting land‐cover change, is occurring at an unprecedented rate. The impact of this thaw on runoff generation in headwater basins is poorly understood. Permafrost thaw has the potential to fundamentally alter the cycling and storage of moisture inputs in this region b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
265
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(275 citation statements)
references
References 35 publications
9
265
1
Order By: Relevance
“…Similar analysis at the Scotty Creek Research Basin near Ft. Simpson (Quinton et al, 2011) showed that the extent of forest-covered permafrost plateaus had decreased by over 38 % in localized areas between 1947 and 2008, with associated collapse of black spruce forest on the plateaus and an increasingly connected surface drainage network. This has the potential to substantially alter basin runoff production in the region (Connon et al, 2014). Further, it has been shown that the rates of permafrost and forested plateau loss have been accelerating, with the average rate of loss in seven different local areas of interest being over 3 times greater during the period -2010compared to 1977(Baltzer et al, 2014.…”
Section: Changes In Permafrostmentioning
confidence: 99%
“…Similar analysis at the Scotty Creek Research Basin near Ft. Simpson (Quinton et al, 2011) showed that the extent of forest-covered permafrost plateaus had decreased by over 38 % in localized areas between 1947 and 2008, with associated collapse of black spruce forest on the plateaus and an increasingly connected surface drainage network. This has the potential to substantially alter basin runoff production in the region (Connon et al, 2014). Further, it has been shown that the rates of permafrost and forested plateau loss have been accelerating, with the average rate of loss in seven different local areas of interest being over 3 times greater during the period -2010compared to 1977(Baltzer et al, 2014.…”
Section: Changes In Permafrostmentioning
confidence: 99%
“…In both alpine and northern wetlands, the existence of thick soil organic layers plays a large role in regulating hydrological sensitivity (including changes in surface ET) to climate warming due to high porosity and hydraulic conductivity of organic soil [54]. In addition, the existence of permafrost helps maintain high water tables and enhance soil saturation even under relatively dry climate conditions by limiting water infiltration to deep soil layers [58]. However, warming-induced permafrost degradation may have a much larger impact on the surface hydrology of northern wetlands underlain by greater permafrost coverage, while the potential influence of warming-induced permafrost thaw on TP wetlands is likely limited due to only sparse permafrost cover in these areas [46,59].…”
Section: Implication Of Climate Warming In Alpine Wetlandsmentioning
confidence: 99%
“…However, warming-induced permafrost degradation may have a much larger impact on the surface hydrology of northern wetlands underlain by greater permafrost coverage, while the potential influence of warming-induced permafrost thaw on TP wetlands is likely limited due to only sparse permafrost cover in these areas [46,59]. For example, permafrost thaw may change the hydrological connectivity of northern wetlands, and increase surface/subsurface runoff [58,60,61], while similar impacts of permafrost thaw in TP wetlands are expected to be minimal.…”
Section: Implication Of Climate Warming In Alpine Wetlandsmentioning
confidence: 99%
“…A reduced snow cover period can result in smaller and slower snowmelt, larger evapotranspiration losses and reduced sublimation losses from headwater basins in cold regions Rasouli et al, 2015). Permafrost thaw can impact regional and local hydrology by increasing surface and subsurface connectivity and baseflow (Connon et al, 2014;Liljedahl et al, 2016;Walvoord and Kurylyk, 2016). Increases in vegetation cover and density have been observed and are especially pronounced near the tundra-taiga ecozone transition (Lantz et al, 2013;Myers-Smith et al, 2011;Sturm et al, 2001;Tape et al, 2006;Xu et al, 2013); however, the impact on the hydrology of these transition Arctic basins is poorly understood.…”
Section: Introductionmentioning
confidence: 99%